2020
DOI: 10.1080/0142159x.2020.1748183
|View full text |Cite
|
Sign up to set email alerts
|

Using a self-regulated learning-enhanced video feedback educational intervention to improve junior doctor prescribing

Abstract: SRL-enhanced video feedback is effective for improving prescribing competency and developing SRL processes such as goal setting and selfmonitoring skills in simulated clinical encounters. Further research is required to evaluate transferability to other clinical sub-speciality contexts and investigate the effectiveness of the intervention for improving prescribing in non-simulated settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
(65 reference statements)
0
3
0
Order By: Relevance
“… 41 Due to this, several interview participants believed it would be more efficient if pharmacists could plan the discharge reconciliation for checking and signoff by the doctors, rather than the other way round. Although pharmacists performing discharge reconciliations are associated with a significant reduction in medicine errors, 42 this may reduce a junior doctor's opportunity to develop their medicine and prescribing knowledge 43 and needs to be considered in terms of the pharmacy workforce.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Due to this, several interview participants believed it would be more efficient if pharmacists could plan the discharge reconciliation for checking and signoff by the doctors, rather than the other way round. Although pharmacists performing discharge reconciliations are associated with a significant reduction in medicine errors, 42 this may reduce a junior doctor's opportunity to develop their medicine and prescribing knowledge 43 and needs to be considered in terms of the pharmacy workforce.…”
Section: Discussionmentioning
confidence: 99%
“…junior doctors) and settings (hospital), where feedback was provided as fortnightly "good prescribing tip" emails to all intern prescribers. Whilst other intervention studies that have demonstrated improved prescribing outcomes, used simulation [36,37] or video methods [25]. The advantage of our intervention is that it was grounded in practice, where prescribing occurs, and so accounts for the highly complex and unpredictable context of prescribing in hospitals [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Our study focused on junior doctors as the main prescribers in hospitals, but in the UK, independent nurses and pharmacist prescribers also have an important role, thus provision of prescribing feedback to multiprofessional prescribers should be explored. Future educational interventions could consider combining individualised EP feedback data with modern initiatives including simulation and video-stimulated feedback 13 32…”
Section: Discussionmentioning
confidence: 99%